Study on light aging of anhydride-cured epoxy resin used for RGB LED packaging material. (December 2019) - Deng, Zhentao; Wang, Mingliang; Zhu, Caizhen; Li, Cuihua; Liu, Jianhong; Tu, Menglong; Xie, Ling; Gui, Dayong
Abstract: RGB LED is widely used in white light illumination and display fields due to its high luminous efficiency and full color display. However, the color drift will occur when RGB LED is used for a long time. In this paper, the luminous performance of RGB LED encapsulated by epoxy materials during longtime lighting and the aging mechanism of methyl hexahydrophthalic anhydride (MHHPA) cured diglycidyl ether of bisphenol-A (DGEBA) were studied by Array spectrometer, ATR-FTIR, XPS and quantum-chemistry calculation. Firstly, the analysis of the lumen maintenance and forward voltage of RGB LED lamps showed, the color drift might be attributed to the degradation of its epoxy materials caused by blue light. FTIR Spectroscopy showed that the aging of packaging materials mainly occurred on the surface of blue LED lamps, where active hydrogen of secondary and tertiary carbon might be oxidized to carbonyl groups due to O2 or peroxy groups in the air. And the aging of epoxy materials also might include the chain scission or the rearrangement reactions of C–O-Ph. XPS results further manifested the decrease of C–C group and increase of C–O and CO group were mainly caused by the chain scission of C–C, C–O-Ph or the ester groups and the oxidation of active hydrogen. And several possible aging reactions were given from the analysis of ATR-FTIR and XPS characterization. The results of quantum-chemistry calculation indicated that C–O bond in C–O-Ph of DGEBA/MHHPA epoxy system was more easily to be broken down during blue light aging, which further verified the results of IR and XPS characterization. Highlights: RGB LED experienced color drift due to the degradation of packaging materials that caused by blue light. Both ATR-FTIR and XPS were used to analyze the variation of the group content. Blue light aging caused the oxidation of active hydrogen and the chain scission of C–C, C–O-Ph or the ester groups. Quantum-chemistry calculation was used to further verify the results of IR and XPS. The C–O bond of C–O-Ph was more easily to be broken down from the results of quantum-chemistry calculation.